Antimicrobial use and stewardship practices on Australian beef feedlots. Issue 1 (12th November 2019) - Badger, SM; Sullivan, KF; Jordan, D; Caraguel, CGB; Page, SW; Cusack, PMV; Frith, D; Trott, DJ
Abstract : Objective: Improving antimicrobial stewardship in the livestock sector requires an understanding of the motivations for antimicrobial use and the quantities consumed. However, detailed information on antimicrobial use in livestock sectors is lacking. This cross‐sectional study aimed to better understand antimicrobial use in the beef feedlot sector in Australia. Design: A self‐administered questionnaire asking about antimicrobial use and reasons for use was designed and mailed to beef feedlot operators in Australia. Respondents were asked to report the percentage of animals treated, purpose of use, and disease conditions targeted for 26antimicrobial agents. Results: In total, 83 of 517 (16.1%) beef feedlot operators completed the survey. Monensin (61.0%of respondents) and virginiamycin (19.5%of respondents) were the most commonly reported in‐feed antimicrobials. In‐feed antimicrobial agents were most frequently used by respondents for treatment of gastrointestinal diseases (52.8%). Antimicrobials were used for growth promotion by 42.1% of respondents, with most (85.7%) reporting the use of ionophores(a group of compounds not used in human medicine). Short‐acting penicillin(69.1%), short‐acting oxytetracycline, and tulathromycin (both 57.3%) werethe most common injectable antimicrobial agents used. Injectable antimicrobials were most frequently used to treat respiratory (72.3%) and musculoskeletal (67.5%) conditions. Conclusion: Overall, the use of antimicrobials was appropriate for the purpose indicated, and there was a strong preference for drugs of low‐importance in human medicine. The data described here stand to be a strong influence on the implementation of an antimicrobial stewardship program in the sector.